Drones and the Creative Industry Innovative Strategies for European SMEs (Springer International Publishing, 2018)
This open access, interdisciplinary book presents innovative strategies in the use of civil drones in the cultural and creative industry. Specially aimed at small and medium-sized enterprises (SMEs), the book offers valuable insights from the fields of marketing, engineering, arts and management. With contributions from experts representing varied interests throughout the creative industry, including academic researchers, software developers and engineers, it analyzes the needs of the creative industry when using civil drones both outdoors and indoors. The book also provides timely recommendations to the industry, as well as guidance for academics and policymakers.